Plan de mejoras por medio de la metodología 5S en el área de producción de la empresa Molinos Poultier S.A. - Arcentales Tobar, Gabriela Elizabeth (2020)
The research analyzes the possibility to apply a continuous improvement methodology in the production area of the Molinos Poultier S.A Company. This is one of the industries with more than 155 years in the market. The Aim of this research is to create a manual that contains key guidelines for the implementation of a system that its aims are to classify, organize, clean, standardize processes and improve the level of discipline of users. The methodology used for this research is based on a qualitative approach because individuals are taken in to account first and the context in which they develop. The research was based on theoretical knowledge that was applied for the benefit of the research. This research has taking as reference or support books, magazines, documents, among other information sources that served as the basis for decision-making. The research found that the Molinos Poultier S.A. Company It is an icon in the province of Cotopaxi, and the Company has been developing programs for its stability, but there are mechanisms that can help it improve even more. Achieving quality in its processes and an ideal working environment for its collaborators should be one of its main objectives. Currently many companies are adopting improvement mechanism that are continuous and easy to apply that result in successful companies, this is the goal of this research, to show that there are simple systems to apply that reach much more educated and successful industries